Brief Report: Disclosure, Consent, Opportunity Costs, and Inaccurate Risk Assessment Deter Pediatric HIV Testing. (1st April 2018) - Wagner, Anjuli D.; O'Malley, Gabrielle; Firdawsi, Olivia; Mugo, Cyrus; Njuguna, Irene N.; Maleche-Obimbo, Elizabeth; Inwani, Irene W.; Wamalwa, Dalton C.; John-Stewart, Grace C.; Slyker, Jennifer A.
Abstract : Background: Prompt child HIV testing and treatment is critical; however, children are often not diagnosed until symptomatic. Understanding factors that influence pediatric HIV testing can inform strategies to increase testing. Methods: A mixed-methods study was conducted at a tertiary hospital in Nairobi, Kenya. Three focus group discussions with health care workers (HCWs) and 18 in-depth interviews with HIV-infected adults with children of unknown status were analyzed using thematic analysis. A structured questionnaire was administered to 116 HIV-infected caregivers of children of unknown status to triangulate qualitative findings. Results: Analysis revealed 3 key periods of the pediatric HIV testing process: decision to test, test visit, and posttest. Key issues included: decision to test: inaccurate HIV risk perception for children, challenges with paternal consent, lack of caregiver HIV status disclosure to partners or older children; test experience: poor understanding of child consent/assent and disclosure guidelines, perceived costs of testing and care, school schedules, HCW discomfort with pediatric HIV testing; and posttest: pessimism regarding HIV-infected children's prognosis, caregiver concerns about their own emotional health if their child is positive, and challenges communicating about HIV with children. Concerns about all 3 periods influenced child testing decisions. In addition, 3 challenges were unique to pediatric HIV: inaccurate HIV risk perception for children; disclosure, consent, and permission; and costs and scheduling. Conclusions: Pediatric HIV testing barriers are distinct from adult barriers. Uptake of pediatric HIV testing may be enhanced by interventions to address misconceptions, disclosure services, psychosocial support addressing concerns unique to pediatric testing, child-focused HCW training, and alternative clinic hours. Abstract : Supplemental Digital Content is Available in the Text.